Analisis Kemampuan Berpikir Kritis pada Buku Bahasa Indonesia Kelas X Sekolah Penggerak dan SMK Pusat Keunggulan - Arwan, Juwintar Febriani; Hasan, Said Hamid; Arifin, Zainal; Kustiah, Hariani (Universitas Pendidikan Indonesia, 2023)
Critical thinking has become a discussion in education as a skill that must be possessed by students so that learning activities properly direct assignment activities and questions that lead to critical thinking skills. Then in this study the aim was to describe the results of the analysis and evaluation of critical thinking in class X Indonesian books used in Sekolah Penggerak dan SMK Pusat Keunggulan. The research method used was content analysis supported by statistic descriptions. The instrument used is a critical thinking activity framework in language learning developed by Ilyas. Based on the results of the analysis, out of 220 assignment activities and questions, there were 137 (62.27%) activities that lead to critical thinking skills, consisting of requests (13.64%); exploring assumptions (14.09%); exploring reasons and proof (13.64%); exploring point of view or perspective (5.45%); exploring impacts, consequences, and alternatives (5.91%); formulate questions (0.91%); predict (0.91%); express agreement and disagreement (3.18%); and summarizing and concluding (4.55%). Based on the proportion of instructions or assignments, this Indonesian language book is sufficient to contain instructions for improving critical thinking skills. However, it takes the teacher's ability to direct learning so that the goal of increasing critical thinking can be developed.